2019
DOI: 10.3390/app9194118
|View full text |Cite
|
Sign up to set email alerts
|

A Traceable High-Accuracy Velocity Measurement by Electro-Optic Dual-Comb Interferometry

Abstract: An electro-optic dual-comb Doppler velocimeter for high-accuracy velocity measurement is presented in this paper. The velocity information of the object can be accurately extracted from the change of repetition frequency, which is in the microwave frequency domain and can be locked to an atomic clock. We generate two optical combs by electro-optic phase modulators and trace their repetition frequencies to the rubidium clock. One functions as the measurement laser and the other the reference. Experimentally, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The proposed setup uses an optical power measurement scheme, i.e., as opposed to measurement of wavelength, and thus would be relatively cheaper when compared to the utilization of complex optical spectrum analyzers for the target application. Moreover, two additional research papers presented by Xie et al [4] and Xue et al [5] have also been categorized under the rubric "fiber optic sensing". For instance, Xie et al [4] reported the application of an integrated optical electric-field sensor on the measurements of transient voltages in AC high-voltage power grids.…”
Section: Fiber Optical Sensingmentioning
confidence: 99%
“…The proposed setup uses an optical power measurement scheme, i.e., as opposed to measurement of wavelength, and thus would be relatively cheaper when compared to the utilization of complex optical spectrum analyzers for the target application. Moreover, two additional research papers presented by Xie et al [4] and Xue et al [5] have also been categorized under the rubric "fiber optic sensing". For instance, Xie et al [4] reported the application of an integrated optical electric-field sensor on the measurements of transient voltages in AC high-voltage power grids.…”
Section: Fiber Optical Sensingmentioning
confidence: 99%
“…Therefore, research on the measuring method of the projectile's velocity and how to improve the measuring accuracy of the projectile's velocity have always been the key contents in the field of the weapon's performance evaluation [5][6][7]. At present, the measuring methods of the projectile's velocity are mainly to use interval velocity measuring devices [8][9][10][11]. The laser screen velocity measuring (LSVM) system is a typical interval velocity measuring device.…”
Section: Introductionmentioning
confidence: 99%
“…As the demands for high-speed and large bandwidth information processing are increasing, electro-optic (EO) devices such as modulators, sensors, deflectors, multipliers, switches, and spatial light modulators, which are developed using EO effect, are gaining important applications in data processing and signal transmission [1][2][3][4][5][6]. EO coefficients are quantitative parameters of the EO effect, their accurate measurements are the key for designing these EO devices, and a study on the dispersion of the EO coefficients is of great significance for designing the EO devices that are suitable for wide spectrum applications [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%